Penentuan kriteria desain pengukus singkong menggunakan Fuzzy-QFD - R. Arief Firmansyah; Khoirul Hidayat (Jurnal Pendidikan Teknologi Pertanian, 2022)
Krepek tette is one of the traditional chips from Pamekasan. Generally, this product is a famous souvenir from the city. This product is usually produced by a small-medium enterprise (SME). In the krepek tette industry, the steaming process is dependent on wood as fuel. The condition makes the steaming process contributes significantly to the resulting carbon footprint. To support sustainable development goals (SDGs), explicitly ensuring sustainable consumption and production pattern. The production process technology in SMEs needs to be upgraded to achieve sustainable production. One of the solutions is to re-design the steamer for the steaming process of raw cassava. To achieve a good steamer design, gathering information about customer need is a fundamental step to accomplish. The research aims to investigate criteria steamer design that meets customer needs. The survey gathered data about customer requirements and pointed to employees in the krepek tette industry located in central production, Blumbungan sub-district, Pamekasan. All qualitative data were analyzed using fuzzy logic to quantify the value of customer requirements and engineering characteristics. House of Quality, the first matrix of QFD, was used to obtain engineering characteristics priority. There was 12 attribute of customer requirements; however, one attribute failed to meet minimum customer importance weight criteria. Translating customer requirements to engineering characteristics obtain ten attributes. Using fuzzy logic to rank engineering characteristics that meet customer requirements, obtain eight attributes for the design criteria of cassava steamer. The attributes were ignition system used heat element, stainless steel, the design used modular systems, used LPG fuel, input, and output process from the same side, temperature and steam disperse equally, and used under steam pressure